Student Perceptions of a Trial of Electronic Text Matching Software: A Preliminary Investigation - Green, D.; Lindemann, I.; Marshall, K.; Wilkinson, G. (Journal of University Teaching and Learning Practice, 2005)
It is accepted that using electronic detection methods has benefitswithin an overall strategy to promote academic integrity in aninstitution. Little attention has been paid to obtaining studentperceptions to evaluate the cost/benefit of using such methods. Thisstudy reports on the evaluation of a trial of Turnitin software. 728students responded to a survey about their thoughts on plagiarismand being involved in the trial. This study found that students weregenerally unsure about the benefits and whether the university shoulduse the software. In particular, two groups of students showedsignificant differences to the rest of the students sampled. While NonEnglish Speaking Background (NESB) students reported higherlevels of perceived usefulness of the software, they also reportedhigher levels of anxiety about the impact on them. Law studentsreported lower levels of perceived usefulness of the software andhigher levels of concern and mistrust. The impact of such perceptionson the learning environment needs to be investigated. Specialattention may be needed in introducing such software to differentgroups of students in order to limit possible deleterious effects andenhance potential benefits.